2007
DOI: 10.1074/jbc.m604143200
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin E Deficiency Induces a Novel Form of Lysosomal Storage Disorder Showing the Accumulation of Lysosomal Membrane Sialoglycoproteins and the Elevation of Lysosomal pH in Macrophages

Abstract: Cathepsin E, an endolysosomal aspartic proteinase predominantly expressed in cells of the immune system, has an important role in immune responses. However, little is known about the precise roles of cathepsin E in this system. Here we report that cathepsin E deficiency (CatE ؊/؊ ) leads to a novel form of lysosome storage disorder in macrophages, exhibiting the accumulation of the two major lysosomal membrane sialoglycoproteins LAMP-1 and LAMP-2 and the elevation of lysosomal pH. These striking features were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…Since an elevated pH is known to induce abnormal properties of endolysosomal compartments including abnormal processing and targeting of lysosomal proteins (10,11) and abnormal maturation and/or fusion events of the acidic organelles (12), CatE -/-macrophages are assumed to show trafficking defects in both membrane and soluble proteins. Indeed, we found the enhanced secretion of soluble lysosomal enzymes by CatE -/-macrophages (9). In addition to soluble proteins, we reported decreased surface levels of Toll-like receptors (TLRs), which are capable of recognizing specific components of microorganisms, in CatE -/-macrophages, further we reported diminished cytokine production by CatE -/-macrophages that are stimulated by specific TLR ligands (8).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Since an elevated pH is known to induce abnormal properties of endolysosomal compartments including abnormal processing and targeting of lysosomal proteins (10,11) and abnormal maturation and/or fusion events of the acidic organelles (12), CatE -/-macrophages are assumed to show trafficking defects in both membrane and soluble proteins. Indeed, we found the enhanced secretion of soluble lysosomal enzymes by CatE -/-macrophages (9). In addition to soluble proteins, we reported decreased surface levels of Toll-like receptors (TLRs), which are capable of recognizing specific components of microorganisms, in CatE -/-macrophages, further we reported diminished cytokine production by CatE -/-macrophages that are stimulated by specific TLR ligands (8).…”
Section: Introductionmentioning
confidence: 76%
“…Recently, we demonstrated that peritoneal macrophages derived from CatE -/-mice display a novel type of lysosomal storage disorder characterized by the accumulation of major lysosomal membrane sialoglycoproteins such as lysosome-associated membrane protein (LAMP)-1 and LAMP-2, in the cells with a concomitant elevated lysosomal pH (9). Since an elevated pH is known to induce abnormal properties of endolysosomal compartments including abnormal processing and targeting of lysosomal proteins (10,11) and abnormal maturation and/or fusion events of the acidic organelles (12), CatE -/-macrophages are assumed to show trafficking defects in both membrane and soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type and CatE -/-mice with the C57BL/6 genetic background were used as described previously [7,8]. Animals were maintained under specific pathogen-free conditions according to the guidelines of the Japanese Pharmacological Society.…”
Section: Micementioning
confidence: 99%
“…Recently, we reported that macrophages derived from CatE -/-mice display a novel type of lysosomal storage disorder, characterized by accumulation of lysosomal membrane glycoproteins such as LAMP-1 and LAMP-2, in cells with a concomitant elevated lysosomal pH [8]. In particular, CatE -/-macrophages exhibit various abnormalities, such as reduced bactericidal activity [9], trafficking defects for both membrane and soluble proteins [10], and impaired TNF-α or IL-6 production [9].…”
Section: Introductionmentioning
confidence: 99%
“…CTSE deficiency also is associated with a novel form of lysosomal storage disorder in macrophages [6]. A related protease, cathepsin D, has been implicated in the degradation of extracellular matrix proteins [7].…”
mentioning
confidence: 99%